Inovasi Pengelolaan Tutup Botol Bekas Menjadi Barang Sebaguna Menuju Sekolah Adiwiyata - Midya Yuli Amreta; Nurul Afidah; Della Nisa'ul Mufida; Ira Rahmawati; Luluk Nurul Aini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Plastic waste, especially bottle caps, is a crucial environmental problem in school environments. Although the Adiwiyata Program has been implemented, obstacles are often encountered in the form of a lack of applicable, interesting, and educational waste management innovations for students. This study aims to develop and evaluate innovations in managing used bottle caps into multipurpose items (sorting trash cans and tissue boxes) as a real contribution towards Adiwiyata Schools. Using a qualitative approach with a case study method involving four main stages: (1) problem identification through interviews and observations; (2) collection of raw materials and designing a participatory design with the theme